FISCAL FACILITIES TO IMPROVE EXPORT PERFORMANCE - Situmorang, Erwin (Dinasti Publisher, 2020)
The Indonesian government, issued a number of policies to help exporters to be able to compete in the world market by exempting import duties or returning import duties on imported goods for export purposes in the form of Bonded Zone and KITE.The policy is aimed at attracting foreign investment and increasing exchange rates, as a laboratory for economic reform and technology transfer, as well as increasing labor force in unproductive areas. Providing facilities provided by the government During 2017 to 1,606 companies valued at Rp 57.28 T from that year. In that year, the total value of exports produced was Rp. 780.8 T, or covering 47.23% of the total national manufacturing exports. The existence of KB and KITE facilities has stimulated the formation of gross fixed capital of IDR 178.17 trillion throughout 2017. From the spillover effect, companies receiving facilities in KB and KITE involve as many as 95,251 business networks, including 68,234 in KB that absorb labor 1.13 million people work and 27,017 business networks in KITE with a workforce of 292.2 thousand people. The presence of companies in KB and KITE contributed to the creation of indirect economic activity of 268,508 businesses, the majority of companies that obtain KB and KITE facilities come from the Western Region of Indonesia, where the number of recipients is concentrated in Java with the largest percentage of companies receiving facilities of 90.35 percent. While, West Java is the province with the largest percentage of KB and KITE facility recipients, which is around 43.90 percent. These results are in accordance with current conditions, where West Java Province is a province that has the most industrial estates in Indonesia, namely 25 industrial estates or equivalent to 33.8 percent of the total 74 industrial estates in Indonesia.